PENGARUH PENGUNAAN MEDIA MANIK-MANIK DALAM TATANAN PENDEKATAN MATEMATIKA REALISTIK TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS II SDN 034 TARAI BANGUN KECAMATAN TAMBANG KABUPATEN KAMPAR - Jesi Alexander Alim; Jalinus Jalinus; Purnama Sari (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2014)
Mathematics learning proses which was done by teachers in grade II SDN 034 Tarai Bangundid not use interesting methods that made students pasif because the teacher just explainedtheory without inviting students to find the mathematics concepts and real activity. Thisresearch aims to know whether using beads media on Realistic Mathematics Educationapproach can improve students’ mathematics learning outcomes at II.A of SDN 034 TaraiBangun in 2013/2014 with 26 students. From data analysis of pretest and posttest, thelearning outcomes increased from both classes (experiment and control). In experiment classaverage pretest score increased from 60,95 to 75,42 with improvement percentage 23%.Meanwhile in control class average pretest score increased 55,16 to 58,06 with improvementpercentage 5%. From the explanation above it shows that using beads media on RealisticMathematics Education approach can improve students’ mathematics learning outcomes atII.A of SDN 034 Tarai Bangun. T-test is used to know whether or not significantly differentbetween both classes with t-test and 60 degree of freedom. t count was bigger than absolute t tablethen Ho was rejected, or H1 was accepted. As a conclusion there is a significantly different ofstudents’ outcomes between experiement and control class.Key Words: Beads media, Realistic Mathematics Education approach